KUAT GESER LAPISAN BETON ASPAL DAN PADA PELAT BAJA UNTUK JEMBATAN - Furqon Affandi (Jurnal Jalan-Jembatan, 2008)
Shear strength between asphalt wearing course and layer beneath in pavement structure has an important role. Wearing course distress will occur due to unsatisfactory shear strength such as shoving, craks and REMOVAL of some wearing course. Moreover, adequate shear strength of asphalt mix layer on steel plate deck bridge is required as well. Laboratorydirect shear test was performed to find out the shear strength between asphalt mixes and various coated steel plates to protect against corrosion. Test result using direct shear principles showed that shear strength resulted from different coating on steel plates was not significant. Test result and its analysis indicated that shear strength between wearing course of asphalt mix layers and steel plates is less than shear strength between wearing course and binder course os asphalt mixes. Therefore, a great careful application (spreading and placement) of asphalt mix on steel plate deck bridge must be taken into account. Key words : Shear strength, steel plate, asphalt mixes, coated material, direct shear